Enteropathogenic Escherichia coli Inhibits Phagocytosis - Goosney, Danika L. (American Society for Microbiology, 1999)
Enteropathogenic Escherichia coli (EPEC) interacts with intestinal epithelial cells, activating host signaling pathways leading to cytoskeletal rearrangements and ultimately diarrhea. In this study, we demonstrate that EPEC interacts with the macrophage-like cell line J774A.1 to inhibit phagocytosis by these cells. Antiphagocytic activity was also observed in cultured RAW macrophage-like cells upon EPEC infection. The EPEC antiphagocytic phenotype was dependent on the type III secretion pathway of EPEC and its secreted proteins, including EspA, EspB, and EspD. Intimin and Tir mutants displayed intermediate antiphagocytic activity, suggesting that intimate attachment mediated by intimin-Tir binding may also play a role in antiphagocytosis. Tyrosine dephosphorylation of several host proteins was observed following infection with secretion-competent EPEC but not with secretion-deficient mutants. Dephosphorylation was detectable 120 min after infection with EPEC, directly correlating with the onset of the antiphagocytic phenotype. Inhibition of protein tyrosine phosphatases by pervanadate treatment increased the number of intracellular wild-type EPEC organisms to levels seen with secretion-deficient mutants, suggesting that dephosphorylation events are linked to the antiphagocytic phenotype. No tyrosine phosphatase activity was detected with the EPEC-secreted proteins, suggesting that EPEC induces antiphagocytosis via a different mechanism than Yersinia species. Taken together, the present findings demonstrate a novel function for EPEC-secreted proteins in triggering macrophage protein tyrosine dephosphorylation and inhibition of phagocytosis.